Do South African managers focus on the creation of shareholder value? - Ronald Fasol; Colin Firer (South African Journal of Business Management, 1995)
Self-administered questionnaires were sent to executive level managers of randomly chosen Johannesburg Stock Exchange (JSE) listed companies. Respondents were tested for their understanding and implementation of shareholder value practices. The majority of respondents were at a senior management level. It was found that shareholder value management is still regarded as a financial management tool and not understood to be a framework for the integration of financial and strategic planning using the economic model of the firm. The majority of respondents allocate resources on a project by project basis and use the top-down approach in the setting of financial targets resulting in a concentration of value around a few business units in the company's portfolio. Strategic plans are not generally evaluated according to shareholder value potential. A shortcoming is the use of accrual accounting measures in financial planning and for the setting of performance targets. A limited number of respondents had full financial and operational autonomy in their business units and performance targets were mostly short term (less than three years) in nature.
Keywords: 650